Α‐Secretase cleaved amyloid precursor protein (APP) accumulates in cholinergic dystrophic neurites in normal, aged hippocampus. Issue 7 (29th October 2013) - Yoon, S.‐Y.; Choi, J.‐U.; Cho, M.‐H.; Yang, K.‐M.; Ha, H.; Chung, I. J.; Cho, G. S.; Kim, D.‐H.
Abstract : Aims: Dystrophic neurites are associated with β‐amyloid (Aβ) plaques in the brains of Alzheimer's disease (AD) patients and are also found in some specific areas of normal, aged brains. This study assessed the molecular characteristics of dystrophic neurites in normal ageing and its difference from AD. Methods: We compared the dystrophic neurites in normal aged human brains (age 20–70 years) and AD brains (Braak stage 4–6) by immunostaining against ChAT, synaptophysin, γ‐tubulin, cathepsin‐D, Aβ1–16, Aβ17–24, amyloid precursor protein (APP)‐CT695 and APP‐NT. We then tested the reproducibility in C57BL/6 mice neurone cultures. Results: In normal, aged mice and humans, we found an increase in clustered dystrophic neurites of cholinergic neurones in CA1 regions of the hippocampus and layer II and III regions of the entorhinal cortex, which are the major and earliest affected areas in AD. These dystrophic neurites showed accumulation of sAPPα peptides cleaved from the amyloid precursor protein by α‐secretase rather than Aβ or C‐terminal fragments. In contrast, Aβ and APP‐CTFs accumulated in the dystrophic neurites in and around Aβ plaques of AD patients. Several experiments suggested that the accumulation of sAPPα resulted from ageing‐related proteasomal dysfunction. Conclusions: Ageing‐associated impairment of the proteasomal system and accumulation of sAPPα at cholinergic neurites in specific areas of brain regions associated with memory could be associated with the normal decline of memory in aged individuals. In addition, these age‐related changes might be the most vulnerable targets of pathological insults that result in pathological accumulation of Aβ and/or APP‐CTFs and lead to neurodegenerative conditions such as AD.